Réponses

2013-11-09T15:48:17+01:00
Bonjour,

1) Tu développes (2x-13)(2x-7).

(2x-13)(2x-7) = (2x)*(2x)-(2x)*7 - 13*(2x) +13*7
(2x-13)(2x-7) = 4x² - 14x - 26x + 91
(2x-13)(2x-7) = 4x² - 40x + 91
(2x-13)(2x-7) = f(x).

2) a) f(x) = 0 <==> (2x-13)(2x-7) = 0
<==> 2x-13=0  ou  2x-7=0
<==> x=13/2  ou  x=7/2.

b) f(0) = 0² - 40*0 + 91
f(0) = 91.

c) f(3\sqrt{5})=4\times(3\sqrt{5})^2-40\times(3\sqrt{5})+91\\\\f(3\sqrt{5})=4\times(9\times5)-120\times\sqrt{5}+91\\\\f(3\sqrt{5})=180-120\times\sqrt{5}+91\\\\f(3\sqrt{5})=271-120\sqrt{5}

d) f(x)=91 <==> 4x² - 40x + 91= 91
<==> 4x² - 40x =0
<==> 4x(x-10) = 0
<==> 4x = 0  ou x-10 = 0
<==> x = 0 ou x = 10.

Les antécédents de 91 sont 0 et 10.
pour le c je ne vois pas la reponse et le 2 a) je n'est pas compris